ESL students’ perceptions towards peer feedback in writing: an exploratory study / Nur Syuhada Mohd Radzi - Mohd Radzi, Nur Syuhada (2010)
Peer feedback is known to improve students’ writing proficiency (Chen, 2009; Grami, 2010,). Thus, feedback is crucial for students to be able to write competently. It is also recognized that error correction is something that baffles teacher. Therefore, a study was conducted in an attempt to find other alternatives to teacher corrections. This study examines the effectiveness of using peer review in improving students’ writing quality as well as to explore students’ perception towards peer feedback. This qualitative and quantitative study includes both writing instruction and questionnaire survey. A sample of 28 Form Four ESL students was selected for this study. Findings revealed that peer feedback does improve the quality of students’ writing. The study concludes with some recommendations to include peer feedback in writing instruction.